PENGEMBANGAN MEDIA POP-UP BOOK DIGITAL BERBASIS ETNOMATEMATIKA PADA MATERI BANGUN RUANG UNTUK SISWA KELAS V SEKOLAH DASAR - Siagian, Enzelina Seftiana; Putra, Zetra Hainul; Sari, Intan Kartika (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2026)
This research is a type of Research and Development that aims to develop a product, namely a digital Pop-Up Book learning medium based on ethnomathematics on spatial figures for fifth-grade elementary school students. The development model used in this research and development is the 4-D model. This model has four stages, starting with Define, Design, Development, and Disseminate. This research was conducted at SD Negeri 003 Genduang on fifth-grade students in the odd semester of the 2025/2026 academic year. The data collection techniques used in this study were interviews, validation questionnaires, and practicality questionnaires. The research instruments used have undergone a validation process with validators, while the final research produced a product in the form of an ethnomathematics-based Pop-Up Book learning medium on spatial figures for fifth-grade elementary school students. From the results of the validation and practicality, it can be concluded that the ethnomathematics-based Pop-Up Book learning medium on spatial figures for fifth-grade elementary school students is declared to be highly valid and very suitable for use.